An Investigation of Entrepreneurship Awareness and Skills among Library Information Science Students at Bauchi Metropolitan Universities - Awurdi, Asabe Pera; Mohammed, Rabiu Nurudeen (American International Journal of Social Science Research, 2018)
This study investigates entrepreneurship skills and awareness among library and information science students at Bauchi metropolitan universities. Nigerian government and relevant stakeholders emphasized on the development of entrepreneurship skills and awareness among undergraduate students at universities, polytechnic and colleges of education. This led to setting up agencies like small and medium scale enterprises (SMEDAN), Industrial Training Fund (ITF) and Entrepreneurship centers and clubs in most Nigerian colleges and universities. Hence, it becomes necessary to equip library and information science students with skills required to achieve self-reliance. Bauchi State is one of the 36 States in Nigeria located in the North East Region of the country with only two public universities, ATBU and BASUG. In these universities, library and information science is offered as a degree course. This study uses Primary data where questionnaire was employ as the tool of data collection. Frequencies and Percentages was used to analyzed the respondents  questions asked while  the chi-square X2 analysis was employ to test the stated hypothesis. The result of the study shows that library and information science students are equip with entrepreneurship skills and awareness at Bauchi metropolitan universities. This study therefore conclude that library and information science students are equip with entrepreneurship skills and awareness in the Nigerian universities as it is seen in Bauchi metropolitan universities. The study recommends that relevant stakeholders including government and corporate world should continue to support and promote entrepreneurship skills and awareness among all students of universities in order to brace them up with the challenges in the labour market after graduation. Priorities should also be given to students to undertake practical trainings courses in entrepreneurship areas and students should be encourage carrying out practical assignments and projects based on real life problems pertaining entrepreneurship skills.